Підходи до управління витратами торгівельної галузі - Kvach, Iryna (Dr. Viktor Koval, 2019)
Introduction. The current state of financial and economic government institutions negatively affects  Ukrainian budget execution, and the general trend of deterioration in the standard of living of the people, in general leads to low level of functioning of the enterprise and  their competitiveness, especially in such industry as trade. Aims and tasks. In the conditions of an unstable political and economic situation in commodity market and services to overcome disproportions between operating profit  of some commodity groups of trade enterprise and its added value which indicates depreciation of the capital  invested by owners not only doesn't provide compensation of investments, but also leads to losses because of inflationary processes therefore there is a need for the mutual integration of approaches of management of expenses for assessment. Results. The practical value of application of a method of Activity-based costing (ABC) and Economic Value Added (EVA) in management of expenses not only in creation of a system of accounting of expenses, but also and predictions through new approaches for the analysis for identification of unproductive fields of activity in value creation of a product is proved, including positively influences the growth of business activity for trade enterprises. In the field of innovative approaches the balanced system of indexes (BSI) and EVA methods harmoniously are integrated in processes of costs planning, management of them at the level of departments and in general are distributed among operation processes to responsible persons, which has a positive impact on maximizing capital cost of the enterprise. Conclusions. Application of methods of cost management as uniform system provides chance to distribute expenses on commodity groups and to define  goods which create added value gives the chance to settle the impact of minimum change of influence of a factor  on commodity turnover level due to decrease of unit  cost in life cycle of a product through the analysis of a point of profitability for increase in investment attractiveness.